The fibroblast activation protein alpha as a biomarker of pulmonary fibrosis - Lavis, Philomène; Garabet, Ani; Cardozo, Alessandra Kupper; Bondue, Benjamin (Frontiers in Medicine, 2024)
Idiopathic pulmonary fibrosis (IPF) is a rare, chronic, and progressive interstitial lung disease with an average survival of approximately 3 years. The evolution of IPF is unpredictable, with some patients presenting a relatively stable condition with limited progression over time, whereas others deteriorate rapidly. In addition to IPF, other interstitial lung diseases can lead to pulmonary fibrosis, and up to a third have a progressive phenotype with the same prognosis as IPF. Clinical, biological, and radiological risk factors of progression were identified, but no specific biomarkers of fibrogenesis are currently available. A recent interest in the fibroblast activation protein alpha (FAPα) has emerged. FAPα is a transmembrane serine protease with extracellular activity. It can also be found in a soluble form, also named anti-plasmin cleaving enzyme (APCE). FAPα is specifically expressed by activated fibroblasts, and quinoline-based specific inhibitors (FAPI) were developed, allowing us to visualize its distribution in vivo by imaging techniques. In this review, we discuss the use of FAPα as a useful biomarker for the progression of lung fibrosis, by both its assessment in human fluids and/or its detection by imaging techniques and immunohistochemistry.